A conceptual framework of internet of things for efficient municipal solid waste management and waste to energy implementation. (10th April 2019) - Bhanot, Neeraj; Sharma, Vinay Kumar; Parihar, Aman Singh; Sharma, Manik; Yadav, Manish; Gupta, Harsh
With a population of 1.252 billion, India holds the second position in the world and is one of the fastest developing countries as well. However, like every good thing has to pay a certain cost, the country is now facing an alarming threat of health and environmental problems due to its poor waste management practices. This paper presents a theoretical framework of an integrated approach of solid waste management system in which a waste segregation layout is shown including waste to energy (WtE) application of the refused derived fuel formed in the process. Real-time monitoring of the segregation process and energy extraction process is done using internet of things (IoT) application. Segregation of waste before processing gives an efficient way of waste management and with this framework, one can easily monitor and acquire various information obtained during different stages of segregation and energy extraction process.